Is Social Support Related to Psychological Wellbeing in Working Mother? - Muhammad Ari Arfianto; Mustikasari Mustikasari; Ice Yulia Wardani (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
The number of working mothers has increased significantly in the last decade. Working mothers have a dual role, as caregivers of children and earn a living. The role of a worker adds to the burden and affects the psychological well-being of the mother. Psychological well-being is an indicator of an individual's mental health. Social support are important factors in the psychological well-being of working mothers. The purpose of this study was to analyze relationship between social support and psychological well-being of working mothers. This research used correlational cross sectional study design. 374 working mother in Sidoarjo East Java were taken using accidental sampling technique. Variable was measured using Multidimentional Scale of Perceived Social Support questionair and Ryff’s Scale Psychological Well-Being questionair. Variables were analyzed by pearson correlation. The result of this research showed that social support have significant correlation with psychological well-being (p value 0,000). These results explain the importance of social support factors in improving the psychological well-being of working mothers.